Cellulose acetate nano preservative film and preparation method thereof
By loading chitosan quaternary ammonium salt between hydrotalcite layers and modifying it, the problems of environmental hazards and mechanical strength of traditional vinyl plastic wrap are solved, and the high mechanical strength of cellulose acetate nano plastic wrap is achieved and Antibacterial properties and green and environmentally friendly properties.
Patent Information
- Application Number
- CN202411469482.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-10-21
AI Technical Summary
Traditional vinyl plastic wrap is harmful to the environment, and the increased conductivity of chitosan quaternary ammonium salt during spinning leads to a decrease in the mechanical strength of cellulose acetate plastic wrap.
By loading chitosan quaternary ammonium salt between hydrotalcite layers, using the layered structure of hydrotalcite and the modification of sodium alginate, the chitosan quaternary ammonium salt is avoided in water and the conductivity of the spinning liquid is reduced. And the hydrotalcite layer spacing is increased by sodium dodecyl sulfonate to ensure sufficient intercalation, thereby improving the mechanical strength and antibacterial properties of the plastic wrap.
The mechanical strength of cellulose acetate nano plastic wrap is improved and antibacterial properties are maintained, and the generation of plastic waste is avoided, and it has green and environmentally friendly characteristics.
Smart Images

Figure BDA0005094306970000111 
Figure BDA0005094306970000121 
Figure BDA0005094306970000122
Abstract
Description
Technical Field
[0001] This invention relates to the field of food preservation film technology, and in particular to a cellulose acetate nano-food preservation film and its preparation method. Background Art
[0002] Currently, most food preservation films on the market are plastic products made from ethylene through polymerization. On the one hand, plastic products harm the environment, a phenomenon commonly known as "white pollution." White pollution negatively impacts water, soil, and the atmosphere, harming the health of living organisms and causing various diseases. Cellulose acetate, also known as cellulose acetate resin, is a thermoplastic resin obtained by esterifying the hydroxyl groups of cellulose under the action of a catalyst. Cellulose acetate is a white solid with characteristics such as stability, ease of processing, non-flammability, low price, abundant raw materials, and biodegradability. It can replace traditional ethylene-based raw materials in the production of food preservation films, eliminating plastic waste and making it environmentally friendly. Cellulose acetate films prepared by electrospinning have advantages such as uniform fineness, small fiber diameter, and low porosity. The preparation of nanofiber materials using cellulose acetate via electrospinning technology is a high-tech process that integrates multidisciplinary research, fundamental theoretical research, and novel product development. With its novel microstructure, unique physical and chemical properties unlike traditional bulk materials, and significant value in both basic research and application, it has become a cutting-edge field in nanomaterials science.
[0003] Antibacterial properties are an important performance indicator for food preservation films. Chitosan quaternary ammonium salts, derivatives of chitosan, exhibit excellent antibacterial properties across a wide pH range. They are also non-toxic, odorless, and readily soluble in water, making their application in the food industry safer and more convenient. Therefore, chitosan quaternary ammonium salts are an ideal antibacterial component for cellulose acetate food preservation films. However, chitosan quaternary ammonium salts are cationic polymers. When dissolved in water, they release positively charged ions. These ions increase the conductivity of the solution. Increased conductivity in the spinning solution can cause beading, resulting in smaller fiber diameters and shorter lengths, which reduces the mechanical strength of the cellulose acetate food preservation film. Summary of the Invention
[0004] To overcome the above-mentioned problems of the prior art, the present invention provides a cellulose acetate nano plastic wrap and a method for preparing the same. The cellulose acetate nano plastic wrap prepared by the present invention not only has good antibacterial properties but also has good mechanical strength. To achieve the above-mentioned objectives, the present invention adopts the following technical solutions:
[0005] A method for preparing a cellulose acetate nano-preservative film comprises the following steps:
[0006] 1) adding cellulose acetate to an aqueous acetic acid solution, heating and stirring to dissolve the cellulose acetate solution;
[0007] 2) Add modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution, stir and mix evenly to obtain the spinning solution;
[0008] 3) The spinning solution is sucked into a syringe on a high-voltage electrospinning device, and then a spinning needle is installed on the syringe that has sucked the spinning solution. The high-voltage electrospinning device is turned on to perform electrospinning to form a film, thereby obtaining a cellulose acetate nano preservative film. Cellulose acetate, also known as cellulose acetate, is a thermoplastic resin obtained by esterifying the hydroxyl groups of cellulose under the action of a catalyst. Cellulose acetate is a white solid with the characteristics of being stable, easy to process, not easy to burn, low in price, abundant in raw materials, and biodegradable. The present invention uses cellulose acetate to replace the traditional use of ethylene raw materials to prepare preservative film, does not generate plastic waste, and is environmentally friendly. Chitosan quaternary ammonium salt is used as the antibacterial component of the preservative film. Chitosan quaternary ammonium salt is a derivative of chitosan and has good antibacterial properties under a wide pH range. It is non-toxic, tasteless, and easily soluble in water, making its application in the food field safer and more convenient.
[0009] Preferably, in step 1), the mass concentration of the cellulose acetate solution is 15-20 wt.%.
[0010] Preferably, in step 2), the amount of modified quaternary ammonium salt chitosan antibacterial agent added is 2-5 wt.% of the cellulose acetate solution.
[0011] Preferably, in step 3), the electrospinning conditions are as follows:
[0012] The voltage is 12-15 kV; the spinning solution flow rate is 0.3-0.8 ml / h; and the receiving distance is 7-10 cm.
[0013] Preferably, the preparation method of the modified quaternary ammonium salt chitosan antibacterial agent includes the following steps:
[0014] 21) Add hydrotalcite to anhydrous ethanol, heat and stir until homogeneous to obtain a hydrotalcite suspension;
[0015] 22) Add N,N,N-trimethyl chitosan quaternary ammonium salt to deionized water, heat and stir to dissolve, and obtain N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0016] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 4-5, heat and stir to react, cool and let stand for more than 12 hours, and then filter, wash and dry to obtain the modified quaternary ammonium salt chitosan antibacterial agent.
[0017] Chitosan quaternary ammonium salt is a derivative of chitosan. It has good antibacterial properties relative to chitosan in a wide pH range, and is non-toxic, tasteless, and soluble in water, making its application in the food field safer and more convenient. In the technical solution of the present invention, chitosan quaternary ammonium salt is added to cellulose acetate spinning solution, so that the preservative film prepared by electrostatic spinning has antibacterial properties. However, chitosan quaternary ammonium salt is a cationic polymer. When dissolved in water, the quaternary ammonium salt group ionizes in water to generate cations that can migrate freely. These cations can increase the conductivity of the solution. The increased conductivity of the spinning solution can cause beading in the spinning process, and the spun fiber diameter is small and the length is short, resulting in a decrease in the mechanical strength of the cellulose acetate preservative film. The present invention is for solving the problems of the technologies described above, and chitosan quaternary ammonium salt is modified: hydrotalcite is a kind of anionic layered material, comprises positively charged lamina surface and negatively charged interlayer anion and water molecule in its structure, chitosan quaternary ammonium salt is as a kind of cationic polymer, can be orderly inserted into the interlayer of hydrotalcite by interaction forces such as electrostatic action, hydrogen bond, van der Waals force, form organic-inorganic intercalation composite material, thereby chitosan quaternary ammonium salt is loaded on the interlayer of hydrotalcite, avoid chitosan quaternary ammonium salt to be dissolved in water and ionize out the cation of free migration, reduce the electrical conductivity of spinning solution, thereby avoid beading phenomenon to occur in spinning process, thereby improve the mechanical strength of preservative film. In addition, hydrotalcite has good good dispersibility in spinning solution, thereby makes chitosan quaternary ammonium salt be evenly dispersed in spinning, helps to improve the antimicrobial property of preservative film. As preferably, in described step 21), hydrotalcite is through pre-treatment:
[0018] γ-(2,3-epoxypropoxy)propyltrimethoxysilane was added to a mixed solution of ethanol and water, and then hydrotalcite was added. The mixture was heated and stirred to obtain coupling agent modified hydrotalcite.
[0019] Sodium alginate is added into deionized water and stirred to dissolve to obtain a sodium alginate solution. Coupling agent-modified hydrotalcite is added into the sodium alginate solution, and then potassium hydroxide is added to dissolve and adjust the pH to 9-10. The reaction is heated and stirred, and the solution is obtained after filtering, washing and drying.
[0020] As preferably, described step 22) in N, N, sodium lauryl sulfate is also added in N-trimethyl chitosan quaternary ammonium salt solution.In technical solution of the present invention, as mentioned above, chitosan quaternary ammonium salt is loaded on hydrotalcite interlayer, avoid chitosan quaternary ammonium salt to be dissolved in the water and ionize out the cation of free migration, reduce the electrical conductivity of spinning solution, thereby avoid beading phenomenon in spinning process, thereby improve the mechanical strength of fibrous membrane.But the problem that the present invention team is being loaded on polysaccharide quaternary ammonium salt in hydrotalcite interlayer process and runs into is the hydrotalcite surface positively charged of lamellar structure, positive charge forms electrostatic repulsion force on itself and chitosan quaternary ammonium salt molecule, and hydrotalcite interlayer spacing is less, chitosan quaternary ammonium salt intercalation hydrotalcite is formed hindering effect, adopt common method to have only a small amount of chitosan quaternary ammonium salt molecule intercalation to hydrotalcite interlayer, cause the antimicrobial property of preservative film to decline. Therefore, the present invention team further modified the hydrotalcite: on the one hand, by grafting sodium alginate onto the surface of the hydrotalcite layer, the negative charge of sodium alginate changes the charge of the hydrotalcite surface, preventing the positive charge on the hydrotalcite surface from forming an electrostatic repulsion effect on the chitosan quaternary ammonium salt. On the other hand, by adding sodium lauryl sulfate to the chitosan quaternary ammonium salt solution, the relatively small molecular weight of sodium lauryl sulfate can first enter the hydrotalcite interlayer to intercalate the hydrotalcite, thereby increasing the interlayer spacing of the hydrotalcite. The increased interlayer spacing of the hydrotalcite is beneficial for subsequent further intercalation of the hydrotalcite with chitosan quaternary ammonium salt. Through the above two aspects of modification, the present invention can intercalate a sufficient amount of chitosan quaternary ammonium salt into the hydrotalcite interlayer, thereby maintaining the antibacterial properties of the plastic wrap while simultaneously improving the mechanical strength of the plastic wrap.
[0021] A cellulose acetate nano-preservative film is prepared by the method described above.
[0022] The present invention has the following beneficial effects:
[0023] 1) Using cellulose acetate instead of ethylene as a raw material for making plastic wrap will not generate plastic waste and is green and environmentally friendly;
[0024] 2) Chitosan quaternary ammonium salt is used as the antibacterial component of the plastic wrap. Chitosan quaternary ammonium salt is a derivative of chitosan, has good antibacterial properties in a wide pH range, is non-toxic and odorless, and is easily soluble in water, making its application in the food field safer and more convenient;
[0025] 3) Chitosan quaternary ammonium salt is loaded between the hydrotalcite layers to prevent the chitosan quaternary ammonium salt from dissolving in water and ionizing free-migrating cations, thereby reducing the conductivity of the spinning solution and avoiding the beading phenomenon during the spinning process, thereby improving the mechanical strength of the plastic wrap. Detailed Implementation
[0026] The present invention will be further described clearly and in detail below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.
[0027] Unless otherwise specified, all raw materials used in the embodiments of the present invention are commercially available or obtainable by those skilled in the art; unless otherwise specified, all methods used in the embodiments of the present invention are methods mastered by those skilled in the art.
[0028] Example 1
[0029] The preparation method of cellulose acetate nano-preservative film includes the following steps:
[0030] 1) adding cellulose acetate to a 75% glacial acetic acid aqueous solution, heating to 50° C., and stirring to dissolve to prepare a cellulose acetate solution with a mass concentration of 18 wt.%;
[0031] 2) Add modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution. The amount of modified quaternary ammonium salt chitosan antibacterial agent added is 4 wt.% of the cellulose acetate solution. Stir and mix evenly to obtain the spinning solution.
[0032] 3) The spinning solution is drawn into the syringe of the high-voltage electrospinning equipment, and then the spinning needle is installed on the syringe that has drawn in the spinning solution. The high-voltage electrospinning equipment is turned on to perform electrospinning and film formation. During the spinning process, the voltage is controlled at 14kV, the flow rate of the spinning solution is 0.6ml / h, and the receiving distance is 9cm to obtain cellulose acetate nano-preservative film.
[0033] The preparation method of modified quaternary ammonium salt chitosan antibacterial agent includes the following steps: 21) Add 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of 80mL ethanol and 10mL water, then add 5g of hydrotalcite, heat to 50℃, stir and react for 50min to obtain coupling agent modified hydrotalcite.
[0034] Add 2g of sodium alginate to 100mL of deionized water and stir to dissolve to obtain sodium alginate solution. Add 5g of coupling agent modified hydrotalcite to sodium alginate solution, then add potassium hydroxide to dissolve and adjust the pH to 10. Heat to 60℃ and stir to react for 2h. After filtration, washing and drying, pretreated hydrotalcite is obtained.
[0035] 5 g of pretreated hydrotalcite was added to 150 mL of anhydrous ethanol, heated to 45° C., and stirred to obtain a hydrotalcite suspension; 22) 2 g of N,N,N-trimethyl chitosan quaternary ammonium salt and 0.5 g of sodium lauryl sulfate were added to 100 mL of deionized water, heated to 45° C., and stirred to dissolve to obtain an N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0036] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 5, heat to 60°C, stir and react for 1 hour, cool and let stand for 12 hours, then filter, wash and dry to obtain a modified quaternary ammonium salt chitosan antibacterial agent.
[0037] Example 2
[0038] The preparation method of cellulose acetate nano-preservative film includes the following steps:
[0039] 1) adding cellulose acetate to a 75% glacial acetic acid aqueous solution, heating to 50° C., and stirring to dissolve to prepare a 16% by weight cellulose acetate solution;
[0040] 2) adding a modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution, wherein the amount of the modified quaternary ammonium salt chitosan antibacterial agent added is 3 wt.% of the cellulose acetate solution, stirring and mixing uniformly to obtain a spinning solution;
[0041] 3) The spinning solution was sucked into a syringe on a high-voltage electrospinning device, and then the spinning needle was installed on the syringe that sucked the spinning solution. The high-voltage electrospinning device was turned on to perform electrospinning film formation. During the spinning process, the voltage was controlled at 13 kV, the spinning solution flow rate was 0.4 ml / h, and the receiving distance was 8 cm to obtain a cellulose acetate nano preservative film.
[0042] The preparation method of modified quaternary ammonium salt chitosan antibacterial agent includes the following steps: 21) Add 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of 80mL ethanol and 10mL water, then add 5g of hydrotalcite, heat to 50℃, stir and react for 50min to obtain coupling agent modified hydrotalcite.
[0043] 2 g of sodium alginate was added to 100 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. 5 g of coupling agent-modified hydrotalcite was added to the sodium alginate solution, and then potassium hydroxide was added to dissolve and adjust the pH to 9. The solution was heated to 60°C and stirred for 2 h. The solution was filtered, washed, and dried to obtain a pretreated hydrotalcite.
[0044] 5 g of pretreated hydrotalcite was added to 150 mL of anhydrous ethanol, heated to 45° C., and stirred to obtain a hydrotalcite suspension; 22) 2 g of N,N,N-trimethyl chitosan quaternary ammonium salt and 0.5 g of sodium lauryl sulfate were added to 100 mL of deionized water, heated to 45° C., and stirred to dissolve to obtain an N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0045] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 4, heat to 60℃, stir and react for 1 hour, cool and let stand for 12 hours, then filter, wash and dry to obtain the modified quaternary ammonium salt chitosan antibacterial agent.
[0046] Example 3
[0047] The preparation method of cellulose acetate nano-preservative film includes the following steps:
[0048] 1) Add cellulose acetate to a 75% aqueous solution of glacial acetic acid, heat to 50°C, stir to dissolve, and prepare a cellulose acetate solution with a mass concentration of 17 wt.%.
[0049] 2) Add modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution. The amount of modified quaternary ammonium salt chitosan antibacterial agent added is 3.5 wt.% of the cellulose acetate solution. Stir and mix evenly to obtain the spinning solution.
[0050] 3) The spinning solution is drawn into the syringe of the high-voltage electrospinning equipment, and then the spinning needle is installed on the syringe that has drawn in the spinning solution. The high-voltage electrospinning equipment is turned on to perform electrospinning and film formation. During the spinning process, the voltage is controlled at 13kV, the flow rate of the spinning solution is 0.5ml / h, and the receiving distance is 8cm to obtain cellulose acetate nano-preservative film.
[0051] The preparation method of modified quaternary ammonium salt chitosan antibacterial agent includes the following steps: 21) Add 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of 80mL ethanol and 10mL water, then add 5g of hydrotalcite, heat to 50℃, stir and react for 50min to obtain coupling agent modified hydrotalcite.
[0052] 2 g of sodium alginate was added to 100 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. 5 g of coupling agent-modified hydrotalcite was added to the sodium alginate solution, and then potassium hydroxide was added to dissolve and adjust the pH to 9. The solution was heated to 60°C and stirred for 2 h. The solution was filtered, washed, and dried to obtain a pretreated hydrotalcite.
[0053] 5 g of pretreated hydrotalcite was added to 150 mL of anhydrous ethanol, heated to 45° C., and stirred to obtain a hydrotalcite suspension; 22) 2 g of N,N,N-trimethyl chitosan quaternary ammonium salt and 0.5 g of sodium lauryl sulfate were added to 100 mL of deionized water, heated to 45° C., and stirred to dissolve to obtain an N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0054] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 5, heat to 60°C, stir and react for 1 hour, cool and let stand for 12 hours, then filter, wash and dry to obtain a modified quaternary ammonium salt chitosan antibacterial agent.
[0055] Example 4
[0056] The preparation method of cellulose acetate nano-preservative film includes the following steps:
[0057] 1) Add cellulose acetate to a 75% aqueous solution of glacial acetic acid, heat to 50°C, stir to dissolve, and prepare a cellulose acetate solution with a mass concentration of 20 wt.%.
[0058] 2) adding a modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution, wherein the amount of the modified quaternary ammonium salt chitosan antibacterial agent added is 5 wt.% of the cellulose acetate solution, stirring and mixing uniformly to obtain a spinning solution;
[0059] 3) The spinning solution was sucked into the syringe on the high-voltage electrospinning device, and then the spinning needle was installed on the syringe that sucked the spinning solution. The high-voltage electrospinning device was turned on to perform electrospinning film formation. During the spinning process, the voltage was controlled at 15 kV, the spinning solution flow rate was 0.8 ml / h, and the receiving distance was 10 cm to obtain a cellulose acetate nano preservative film.
[0060] The preparation method of modified quaternary ammonium salt chitosan antibacterial agent includes the following steps: 21) Add 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of 80mL ethanol and 10mL water, then add 5g of hydrotalcite, heat to 50℃, stir and react for 50min to obtain coupling agent modified hydrotalcite.
[0061] Add 2g of sodium alginate to 100mL of deionized water and stir to dissolve to obtain sodium alginate solution. Add 5g of coupling agent modified hydrotalcite to sodium alginate solution, then add potassium hydroxide to dissolve and adjust the pH to 10. Heat to 60℃ and stir to react for 2h. After filtration, washing and drying, pretreated hydrotalcite is obtained.
[0062] 5 g of pretreated hydrotalcite was added to 150 mL of anhydrous ethanol, heated to 45° C., and stirred to obtain a hydrotalcite suspension; 22) 2 g of N,N,N-trimethyl chitosan quaternary ammonium salt and 0.5 g of sodium lauryl sulfate were added to 100 mL of deionized water, heated to 45° C., and stirred to dissolve to obtain an N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0063] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 5, heat to 60°C, stir and react for 1 hour, cool and let stand for 12 hours, then filter, wash and dry to obtain a modified quaternary ammonium salt chitosan antibacterial agent.
[0064] Example 5
[0065] The preparation method of cellulose acetate nano-preservative film includes the following steps:
[0066] 1) Add cellulose acetate to a 75% aqueous solution of glacial acetic acid, heat to 50°C, stir to dissolve, and prepare a cellulose acetate solution with a mass concentration of 15 wt.%.
[0067] 2) adding a modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution, wherein the amount of the modified quaternary ammonium salt chitosan antibacterial agent added is 2 wt.% of the cellulose acetate solution, stirring and mixing uniformly to obtain a spinning solution;
[0068] 3) The spinning solution is drawn into the syringe of the high-voltage electrospinning equipment, and then the spinning needle is installed on the syringe that has drawn in the spinning solution. The high-voltage electrospinning equipment is turned on to perform electrospinning and film formation. During the spinning process, the voltage is controlled at 12kV, the flow rate of the spinning solution is 0.3ml / h, and the receiving distance is 7cm to obtain cellulose acetate nano-preservative film.
[0069] The preparation method of modified quaternary ammonium salt chitosan antibacterial agent includes the following steps: 21) Add 2g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of 80mL ethanol and 10mL water, then add 5g of hydrotalcite, heat to 50℃, stir and react for 50min to obtain coupling agent modified hydrotalcite.
[0070] 2 g of sodium alginate was added to 100 mL of deionized water and stirred to dissolve to obtain a sodium alginate solution. 5 g of coupling agent-modified hydrotalcite was added to the sodium alginate solution, and then potassium hydroxide was added to dissolve and adjust the pH to 9. The solution was heated to 60°C and stirred for 2 h. The solution was filtered, washed, and dried to obtain a pretreated hydrotalcite.
[0071] 5 g of pretreated hydrotalcite was added to 150 mL of anhydrous ethanol, heated to 45° C., and stirred to obtain a hydrotalcite suspension; 22) 2 g of N,N,N-trimethyl chitosan quaternary ammonium salt and 0.5 g of sodium lauryl sulfate were added to 100 mL of deionized water, heated to 45° C., and stirred to dissolve to obtain an N,N,N-trimethyl chitosan quaternary ammonium salt solution;
[0072] 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH to 4, heat to 60℃, stir and react for 1 hour, cool and let stand for 12 hours, then filter, wash and dry to obtain the modified quaternary ammonium salt chitosan antibacterial agent.
[0073] Comparative Example 1
[0074] The difference between Comparative Example 1 and Example 1 is as follows:
[0075] No modified quaternary ammonium salt chitosan antibacterial agent is added during the preparation of cellulose acetate nano-preservative film.
[0076] The remaining operating steps are the same as in Example 1.
[0077] Comparative Example 2
[0078] The difference between Comparative Example 2 and Example 1 is as follows:
[0079] During the preparation of cellulose acetate nano-cling film, the modified quaternary ammonium chitosan antibacterial agent is replaced with N,N,N-trimethyl chitosan quaternary ammonium salt.
[0080] The remaining steps are the same as those in Example 1.
[0081] Comparative Example 3
[0082] The difference between Comparative Example 3 and Example 1 is:
[0083] Sodium alginate is not used to modify hydrotalcite in the preparation of modified quaternary ammonium salt chitosan antibacterial agent.
[0084] The remaining steps are the same as those in Example 1.
[0085] Comparative Example 4
[0086] The difference between Comparative Example 4 and Example 1 is as follows:
[0087] Sodium dodecyl sulfonate is not added to the N,N,N-trimethyl chitosan quaternary ammonium salt solution during the preparation of the modified quaternary ammonium salt chitosan antibacterial agent.
[0088] The remaining steps are the same as those in Example 1.
[0089] Performance Testing
[0090] 1. Antibacterial performance test:
[0091] The antibacterial performance of plastic wrap was verified by performing the antibacterial test method described in GB / T31402. The antibacterial properties of the plastic wrap were verified and the inhibition rate was calculated. The plastic wrap was cut into test samples of 50 mm x 50 mm and placed in a sterile Petri dish. 0.4 mL of the target bacterial solution was accurately pipetted and dripped onto the test sample. The Petri dish was then covered with a lid, inverted, and placed in a biochemical incubator at 37°C for 24 hours. Three independent parallel tests were performed for each set of tests.
[0092]
[0093]
[0094] 2. Mechanical properties test:
[0095] The tensile strength of plastic wrap was tested using the test method in GB / T 1040.3-2006. The composite film was cut into long strips of test specimens measuring 150 mm x 15 mm. Both ends of the test specimens were secured to the fixtures of a universal electronic materials testing machine, set at 50 mm / min, until the specimen broke. Each test was repeated six times independently, and the resulting values were recorded.
[0096]
[0097] The above are merely preferred embodiments of the present invention. It should be noted that the above preferred embodiments should not be construed as limiting the present invention, and the scope of protection of the present invention should be determined by the scope defined in the claims. Persons skilled in the art will appreciate that improvements and modifications may be made without departing from the spirit and scope of the present invention, and such improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a cellulose acetate nano preservative film, characterized in that: The following steps are involved: 1) adding cellulose acetate into an aqueous solution of acetic acid, heating and stirring to dissolve, to obtain a cellulose acetate solution; 2) adding a modified quaternary ammonium salt chitosan antibacterial agent to the cellulose acetate solution, stirring and mixing uniformly to obtain a spinning solution; 3) The spinning solution is sucked into a syringe on a high-voltage electrospinning device, and then a spinning needle is installed on the syringe that sucks the spinning solution, and the high-voltage electrospinning device is turned on to perform electrospinning to form a film, thereby obtaining a cellulose acetate nano preservative film.
2. The method for preparing a cellulose acetate nano preservative film according to claim 1, characterized in that: In the step 1), the mass concentration of the cellulose acetate solution is 15-20 wt.%.
3. The method for preparing a cellulose acetate nano preservative film according to claim 1, characterized in that: In the step 2), the amount of the modified quaternary ammonium salt chitosan antibacterial agent added is 2-5 wt.% of the cellulose acetate solution.
4. The method for preparing a cellulose acetate nano preservative film according to claim 1, characterized in that: In the step 3), the electrospinning conditions are as follows: The voltage is 12-15 kv; the spinning solution flow rate is 0.3-0.8 ml / h; and the receiving distance is 7-10 cm.
5. The method for preparing a cellulose acetate nano preservative film according to claim 1, characterized in that: The preparation method of the modified quaternary ammonium salt chitosan antibacterial agent comprises the following steps: 21) adding hydrotalcite into anhydrous ethanol, heating and stirring to obtain a hydrotalcite suspension; 22) adding N,N,N-trimethyl chitosan quaternary ammonium salt into deionized water, heating and stirring to dissolve, to obtain N,N,N-trimethyl chitosan quaternary ammonium salt solution; 23) Pour the N,N,N-trimethyl chitosan quaternary ammonium salt solution into the hydrotalcite suspension, add dilute nitric acid to adjust the pH value to 4-5, heat and stir to react, cool and let stand for more than 12 hours, then filter, wash and dry to obtain a modified quaternary ammonium salt chitosan antibacterial agent.
6. The method for preparing a cellulose acetate nano preservative film according to claim 2, characterized in that: In the step 21), the hydrotalcite is pretreated: Adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane to a mixed solution of ethanol and water, then adding hydrotalcite, heating and stirring to react, to obtain coupling agent-modified hydrotalcite; Sodium alginate is added into deionized water, stirred and dissolved to obtain a sodium alginate solution, coupling agent-modified hydrotalcite is added into the sodium alginate solution, potassium hydroxide is then added to dissolve and adjust the pH to 9-10, heated and stirred to react, filtered, washed and dried to obtain the product.
7. The method for preparing a cellulose acetate nano preservative film according to claim 2, characterized in that: In the step 22), sodium dodecyl sulfate is also added to the N,N,N-trimethyl chitosan quaternary ammonium salt solution.
8. A cellulose acetate nano preservative film, characterized in that: The method is prepared by the method described in any one of claims 1 to 7.
Citation Information
Patent Citations
Preparation of sodium alginate intercalated hydrotalcite adsorbent and application thereof
CN105854811A
Quaternized chitosan modified bentonite adsorption material, preparation thereof and application of quaternized chitosan modified bentonite adsorption material in adsorption of lead ions in waste water
CN106732425A
Oxidation-resistant cellulose acetate nano fibrous preservative film for food
CN106757464A
Antibacterial ultrafine fiber composite film and manufacturing method thereof
CN109137259A
Polylactic acid composite material with surface modified with drug-loaded layered double hydroxide as well as preparation method and application of polylactic acid composite material
CN114920274A
Cited By
Meat product preservative film and preparation method thereof
CN119913668A
Five-element co-doped porous CoFeCuMnNi-LDH nano material as well as preparation method and application thereof
CN121819864A
